1992
DOI: 10.1073/pnas.89.14.6368
|View full text |Cite
|
Sign up to set email alerts
|

CD5 is phosphorylated on tyrosine after stimulation of the T-cell antigen receptor complex.

Abstract: When T cells are activated by the T-cell antigen receptor, a number of cellular proteins are phosphorylated on tyrosine. We investigated whether any of these proteins were present on the surface of activated T cells. Using the human leukemic T-cell line Jurkat and normal peripheral blood lymphocytes, we identified a 67-kDa cell surface glycoprotein in anti-phosphotyrosine immunoprecipitates, after treatment of the cells with CD3 antibody. When cell lysates were depleted of CD5 by sequential immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
43
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 43 publications
5
43
0
Order By: Relevance
“…Once the TCR-CD3 complex is engaged by ligand, the cytoplasmic domain of CD5 becomes rapidly phosphorylated on tyrosine residues, as are the TCR chains (8,17,44). These tyrosines are present in a potential tyrosine kinase phosphorylation motif (Y-X 11 -Y-XX), which is similar to the immunoreceptor tyrosine activation motifs as found in the TCR and CD3 chains (3,44).…”
mentioning
confidence: 79%
“…Once the TCR-CD3 complex is engaged by ligand, the cytoplasmic domain of CD5 becomes rapidly phosphorylated on tyrosine residues, as are the TCR chains (8,17,44). These tyrosines are present in a potential tyrosine kinase phosphorylation motif (Y-X 11 -Y-XX), which is similar to the immunoreceptor tyrosine activation motifs as found in the TCR and CD3 chains (3,44).…”
mentioning
confidence: 79%
“…Taken It was next of interest to assess whether CD5 was itself phosphorylated in vivo by p56 ck. Previous work by ourselves (9) and others (14) has shown that CD5 is rapidly phosphorylated on tyrosine residues as a result of TcR;/CD3 ligation.…”
mentioning
confidence: 99%
“…In this sense, CD5 shares a number of properties with TcR(. Both can be coprecipitated with TcR4/CD3 in gentle detergents and are rapidly phosphorylated on tyrosine residues in response to TcR(/CD3 ligation (9,14,45). Both TcR~and CD5 possess part of a potential tyrosine * Corresponding author.…”
mentioning
confidence: 99%
“…The precise mechanism by which CD5 inhibits TCR signaling has not been elucidated. However, CD5 is tyrosine-phosphorylated after TCR engagement and associates with several effector molecules that could potentially influence the TCR signaling response, including Cbl, rasGAP, SHP-1, casein kinase 2, and TCR-/ZAP-70 (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%